PROFIL PEDAGANG KAKI LIMA (PKL) YANG BERJUALAN DI BADAN JALAN (STUDI DI JALAN TERATAI DAN JALAN SEROJA KECAMATAN SENAPELAN) - Rholen Bayu Saputra; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The presence of the informal sector is very memgang important role in urbanlife, particularly to show a potential source of income for the residents of the city. Theinformal sector in addition to the provision of employment, the informal sector is alsoits existence towns survive without help even even with dai obstacles because theyadministration in the need of products and services produced by the sector.The problem is in this research is (1) Why hawkers (street vendors) selling onthe road? and (2) How does the government's attitude towards street vendors (PKL) whosell on the road?The purpose of this study was to determine the cause of hawkers (street vendors)selling on the road and to determine the government's attitude towards street vendors(PKL) who sell on the road.Subjects in this study were the street vendors (PKL) who sell at marketsSenapelan Pekanbaru totaling 42 merchants. The approach used in this study is to usequalitative descriptive method, the process of collecting data using interviews,observation and questionnaires. The technique of taking subjects in this study was acensus method.The advice is expected that the author wants to convey to the government to bemore concerned about the street vendors (PKL) in Pekanbaru Senapelan market butespecially the street vendors (PKL) in Pekanbaru Senapelan market that does not haveits own stall. Should the street vendors (PKL) in Pekanbaru Senapelan market can keepselling neighborhoods with no selling on the road.Keyword : Informal Sector, Traditional Market, Cadger